2022
DOI: 10.1126/sciadv.abi7109
|View full text |Cite
|
Sign up to set email alerts
|

Insm1 -expressing neurons and secretory cells develop from a common pool of progenitors in the sea anemone Nematostella vectensis

Abstract: Neurons are highly specialized cells present in nearly all animals, but their evolutionary origin and relationship to other cell types are not well understood. We use here the sea anemone Nematostella vectensis as a model system for early-branching animals to gain fresh insights into the evolutionary history of neurons. We generated a transgenic reporter line to show that the transcription factor NvInsm1 is expressed in postmitotic cells that give rise to various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 85 publications
(149 reference statements)
2
11
0
Order By: Relevance
“…While cnidocytes and neurons have commonly been regarded as sister cell types (Richards & Rentzsch, 2014), our data suggest that neurons and gland cells are actually more closely related and have a common progenitor cell, characterized by Insm1 expression, which supports recent evidence of this relationship (Tournière et al, 2021). This also reveals similarities to the relationships within the interstitial cell lineage in Hydra , where neurons and gland cells have a common progenitor state, while nematogenesis is distinct (Siebert et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…While cnidocytes and neurons have commonly been regarded as sister cell types (Richards & Rentzsch, 2014), our data suggest that neurons and gland cells are actually more closely related and have a common progenitor cell, characterized by Insm1 expression, which supports recent evidence of this relationship (Tournière et al, 2021). This also reveals similarities to the relationships within the interstitial cell lineage in Hydra , where neurons and gland cells have a common progenitor state, while nematogenesis is distinct (Siebert et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…We confirmed this assumption by showing that a subset of progeny cells from Vasa2+/Piwi1+ cells consists of soxB(2) -expressing neural progenitor cells. Previous studies using transgenic reporter lines and single cell RNA-seq analysis have shown that multipotent soxB(2) + neural progenitor cells generate gland cells, neurons and cnidocytes during larval and potentially post-larval development (Richards and Rentzsch, 2014; Steger et al, 2022; Tournière et al, 2022). However, the stem cell populations upstream of such progenitors remain so far unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be evidence of a common evolutionary origin for endoderm and neural cells. This would be supported by recent work suggesting that parts of the digestive system in the cnidaria Nematostella are of ectodermal origin (Steinmetz et al, 2017), and that a common progenitor generates neurons and secretory cells in this species (Tournière et al, 2022) (Steger et al, 2022). A deeper understanding of the GRNs in neural tissue and endoderm will be needed to explore this possibility.…”
Section: Discussionmentioning
confidence: 76%